Peers And Violence In Courtship - Estalita Kelly (Universitas Yudharta Pasuruan, 2020)
Violence in a relationship in the millennial era does not only affect married couples. Dating violence also occurs among students. Based on the results of preliminary research on 40 students at Yudharta Pasuruan University, there were 83% psychological violence, 7% physical violence and 10% sexual violence in dating. This study aims to see the relationship between peers and violence in dating among students at the University of Yudharta Pasuruan. The research sample was 96 subjects. Collecting data using a peer scale and a scale of dating violence. The results show that there is no relationship between peers and dating violence